2010
DOI: 10.1039/b926461b
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive aqueous/LC interfaces using SGLCP-b-polyacrylic acid block copolymers

Abstract: Block copolymers that combine a side-group liquid crystalline polymer (SGLCP) block and a pH-responsive hydrophilic block, poly(acrylic acid) (PAA), are shown to confer pH-dependent anchoring of the director orientation at the aqueous/LC interface. The SGLCP block, poly-(4-cyanobiphenyl-4-oxyundecylacrylate), was chosen based on its ability to influence the director field of the 5CB (4-cyano-4 0 -pentylbiphenyl). At low pH the PAA block collapses and the inherent, planar alignment tendency of 5CB at a water in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 44 publications
1
62
0
Order By: Relevance
“…A strong anionic polyelectrolyte such as salmon fish sperm DNA could be detected with this TEM PDMAEMA grid cell at a wide pH range below the pKa of PDMAEMA with a detection limit of 0.01 wt% because it contains negatively charged phosphate deoxyribose groups throughout its structure regardless of the pH. This simple and inexpensive set-up for non-specific biomaterial detection provides the basic groundwork for developing effective and selective biosensors through the introduction of specific binding groups such as aptamers, antibodies, single-stranded DNA, proteins, peptides, and aptamer-binding RNA into the cell [37].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A strong anionic polyelectrolyte such as salmon fish sperm DNA could be detected with this TEM PDMAEMA grid cell at a wide pH range below the pKa of PDMAEMA with a detection limit of 0.01 wt% because it contains negatively charged phosphate deoxyribose groups throughout its structure regardless of the pH. This simple and inexpensive set-up for non-specific biomaterial detection provides the basic groundwork for developing effective and selective biosensors through the introduction of specific binding groups such as aptamers, antibodies, single-stranded DNA, proteins, peptides, and aptamer-binding RNA into the cell [37].…”
Section: Discussionmentioning
confidence: 96%
“…The TEM grid cell and the flow chamber used in this study was prepared by the same procedure as reported elsewhere [37]. The glass slides were first cleaned using piranha solution (H 2 SO 4 and H 2 O 2 mixture (70/30, v/v)), which reacts violently with organic materials and should therefore be handled with extreme care and stored in closed containers.…”
Section: Preparation Of the Tem Grid Cell And The Flow Chambermentioning
confidence: 99%
See 2 more Smart Citations
“…CAUTION: Piranha solution is extremely corrosive and must be handled carefully. PAA-b-LCP was prepared using the same method reported previously [23]. The molecular weight was PAA(15k)-b-LCP(7k) with a M w /M n of 1.19; the number in parenthesis represents the number average molecular weight (M n ), which was calculated from the gel permeation chromatography (GPC) data of poly(tert-butyl acrylate) (PtBA)-b-LCP using 100% conversion.…”
Section: Methodsmentioning
confidence: 99%